PENGARUH PENGGUNAAN METODE SUKU KATA TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SDN I PLUMBON - Febiyolah, Dwi; Nurhabibah, Prabawati; Wahyuningsih, Asih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the use of the syllable method on the early reading ability of first-grade students of SDN I Plumbon. This study uses a quantitative approach with a pre-experimental design "One Group Pretest - Posttest Design". All first-grade students of SDN I Plumbon, totaling 21 students, were used as samples selected using a purposive sampling technique. Data were collected through oral tests (pretest and posttest) and observations. The pretest results showed an average score of students' early reading ability of 50.24, with most students below the KKTP of 70. The main difficulties faced by students include letter recognition, composing syllables, words, and simple sentences. After the application of the syllable method, the posttest results showed a significant increase with an average score of 76.90. This study has illustrated that the pretest and posttest results in the experimental class have increased and there are significant differences. The results of the study using the Paired Sample T-test and the N-Gain test can be concluded that there is an effect of the use of the syllable method on the early reading ability of first-grade students of SDN I Plumbon.